Wideband and high-order microwave vortex-beam launcher based on spoof surface plasmon polaritons - Lei Zhang (Nature Portfolio, 2021)
Abstract The electromagnetic vortex carrying orbital angular momentum (OAM), which is first studied at optical frequency, has begun to attract widespread attention in the field of radio-frequency/microwave. However, for the OAM mode generated by traditional single antennas, there are problems such as low order and narrow bandwidth, and complex structures such as dual-fed networks may be required. In this paper, based on spoof surface plasmon polariton (SSPP) mode leaky-wave antenna, a single-port traveling-wave ring is proposed to radiate high-order OAM modes working near the cut-off frequency of SSPP state. The achieved 12-order OAM mode within 9.1–10.1 GHz (relative bandwidth of 10.4%) has the main radiation direction close to the antenna surface, forming a plane spiral OAM (PSOAM) wave, which reduces the requirements for mode purity in practical applications. This SSPP ring using periodic units as radiating elements can be an effective radiator for broadband and large-capacity OAM multiplexing communications. The structural characteristics of single feed contribute to the integration of microwave circuits.